Factors influencing addiction in female population of an urban slum area - Sapkal, Ashwini Baburao; Deshpande, Swati Rajesh (International Journal of Research in Medical Sciences, 2020)
Background: The use of certain licit substances like alcohol, tobacco and illicit substances like cocaine, amphetamine, cannabis, etc is termed as substance abuse. Globally, the most prevalent form of tobacco use in women is cigarette smoking. But, in low- and middle-income countries use of smokeless forms is quite common. Aim of the study was to study the factors influencing drug and tobacco addiction in the female population of an urban slum area. Methods: Community-based cross-sectional study conducted on 577 female participants in urban slums of a metropolitan city. A pre-validated semi-structured questionnaire was used. Data analysis was done in SPSS version 22.0 (IBM). Descriptive statistics and chi-square tests for associations were used. Results: The mean age of participants was 44.84±14.99 years and the mean age of onset of addiction was 21.51±6.47 years. Around 70.7% of women were tobacco chewers, 9.4% were smoking bidis and 15.8%were addicted to alcohol. Addiction is the subject of conflict in families of 70(12.1%) women. A most common source of information about the harmful effects of addiction was television and tobacco packets. Almost all women i.e. 555(96.2%) knew that oral cancer was a harmful effect of addiction. Willingness to quit an addiction was seen in 45.8%of women. Conclusions: Addiction in females is a major public health problem which is compounded by their lack of knowledge.